Study on key technology of combined pressure relief and permeability enhancement in low permeability hard coal seam - Yujun ZHOU; Zhenhua LI; Jiacheng LI (Meitan kexue jishu)
Based on the characteristics of high gas content, low permeability, high hardness and composite coal seam in a coal mine in Jiaozuo, and the lack of mining protective layer conditions, in order to improve the punching effect and gas drainage effect; the combined anti-reflection technology of “ loose blasting-mechanical cavitation-hydraulic punching” is innovatively proposed. The ANSYS/LS-DYNA finite element analysis software is used to simulate the crack propagation state under different borehole spacing. The blasting parameters such as charge density, charge structure and charge amount were investigated on site. PFC2D numerical simulation software was used to simulate the fracture development range under different hole diameter. The relationship between the degree of tool opening and closing and water pressure was debugged. The results show that under the guidance of the auxiliary hole, a penetrating fracture surface is generated between the two holes, and the optimal distance between the simulated blasting hole and the auxiliary hole is 4 m; the best charge structure is to use the combined anti-reflection technology to transform the three-volume parallel charge of the drug warehouse, and the reasonable charge density is 1.02 kg/m. The reasonable reaming diameter was determined to be 500 mm by PFC2D simulation. The field test of water pressure and knife arm opening shows that when the water pressure reaches 6 MPa, the hole-making knife arm can be fully opened. After the implementation of the on-site industrial test, Compared with the conventional hydraulic punching measures in the mine, the punching speed is increased by 1.21 times. The punching efficiency is increased by 1.23 times, and the amount of coal flushing per meter of borehole is increased by 1.09 times. The initial value, 60 d value and 120 d value of the extraction concentration increased by 20%, 14% and 16% respectively. Combined with numerical simulation and field industrial test results, it is proved that the proposed combined antireflection technology can improve the unching effect and extraction concentration in low permeability hard coal, which provides a reference for gas control in other low permeability hard coal seams.